SYSTEMATIC LITERATURE REVIEW (SLR): THE ANALYSIS OF THE JUVENILE DELINQUENCY TRIGGER FACTORS AND THE HANDLING EFFORTS - sulthon, sulthon; Munir, Muh Misbahul (Universitas Muhammadiyah Purwokerto, 2024)
Â Adolescence is a stage in development experienced by individuals that is different from previous periods. In this period individuals face puberty which is marked by the transition from childhood to adulthood. At this time, teenagers face doubt, uncertainty, emotional instability, so that their actions often deviate from values and norms, this deviation is influenced by many aspects both from within and from outside. The aim of this research is to identify, analyze, study and conclude the factors that trigger juvenile delinquency and efforts to overcome it. The method used in the research is library research with a systematic literature review (SLR) approach. Data collection was carried out using journal search techniques with the keywords